Chapter Solar Deities in the Kuwattalla Ritual Tradition: Epithets and Functions - Mouton, Alice (Studia Asiana, 2023)
Through the contextual analysis of the occurrences of solar deities in the Kuwattalla ritual texts, we will try to sketch a portrait of these deities, focusing on their functions in the ritual process. Special attention will be paid to the combination of ritual gestures with Luwian incantations, since the latter might help to define the specificities of each member of this divine group.